PERAN MAJELIS ULAMA INDONESIA PADA MASA ORDE BARU 1975-1998 DAN RELEVANSINYA DALAM PEMBELAJARAN SEJARAH - Wibowo, Subekty; Joebagio, Hermanu; Bachri, Saiful (Program Studi Pendidikan Sejarah FKIP Unversitas Sebelas Maret, 2018)
The purpose of this research were to describe: (1) the background of the establishment of Ulama Council of Indonesia; (2) the role and position of Ulama Council of Indonesia; (3) the role of Ulama Council in established the Islamic discource in Indonesian New Order 1975-1998; (4) the role of Ulama Council in established the Islamic discource in Indonesias New Order 1975-1998 and its relevance in historical learning at class XII of senior high school.This research used historical method, there are four phases of research procedure, and they are heuristics, critics, interpretations, and historiography. Technique of analyzing the data used historical analysis, give priority to criticsm sharpness and data interpretation. The source of this research used primary resource and secondary resource.The result of this research are: (1) MUI was established by New Order government to muffle the conflict and to create a harmony and cooperations among Muslims and government (2) MUI developed a mainstream religious discources with their authority to created fatawas (3) Reviewing MUI?s history in Indonesias New Order and it?s fatawas about religious sect which can be used as relevant course to look for new paradigm to create a harmony in Indonesian plural society.